SOCIO-ECONOMIC IMPACT OF HUMAN-WILDLIFE CONFLICTS ON AGRICULTURE BASED LIVELIHOOD IN THE PERIPHERY OF SAVE VALLEY CONSERVANCY, SOUTHERN ZIMBABWE - Patience Mhuriro-Mashapa; Emmanuel Mwakiwa; Clayton Mashapa (Journal of Animal and Plant Sciences, 2018)
Human-wildlife conflicts are a concern in southern Zimbabwe which is part of Greater Limpopo Transfrontier Conservation Area. Study objectives were to assess cost value of crop/livestock loss incurred by farmers as well as to identify drivers of human-wildlife conflicts and explore mitigation measures on agro-based communities of Mutema- Musikavanhu, adjacent to Save Valley Conservancy in southern Zimbabwe. Data collection was done in November 2016, using questionnaires administered to randomly selected 300 households and 20 key informants. Majority of farmers ( 86%, n = 258) had incurred annual household economic loss ranging from US$ 671.00 to US$ 998.21 per household, though perceived and actual losses differed by 63.2% for mono-specific stands of crops and livestock herds for the period October 2014 to October 2016. It was concluded the main drivers of human-wildlife conflicts were African elephants (Loxodonta africana) raiding crops like maize ( Zea mays), bananas (Musa sapientum) and legumes (Cucurbita sp.), whereas, lions ( Panthera leo) kill livestock, mainly cattle (Bos taurus). Ineffective deterrents such as setting fires around fields at night, guarding crops and herding livestock were methods employed to minimize human- wildlife conflicts. Local people suggested erection of an electrified fence to reduce trespassing of wild animals from protected area to human settlement. challenges faced by communal farmers, inclusive of
Keywords: agriculture; conflicts; communal area; livelihood; protected area; Save Valley Conservancy; wild animals